PENGARUH PENDIDIKAN, UMUR DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. ANELA KM 79 KABUPATEN LAMONGAN - Arul Dicky Permana; Muhammad Mansur; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted at PT. Anela km 79 Regency of Lamongan. The purpose of this study was to examine and analyze the effect of Education, Age and Work Experience on Employee Productivity at PT. Anela km 79 Regency of Lamongan.The variables used are Education, Age and Work Experience as an independent variable, while the Employee Productivity variable is the dependent variable. The sample used in this study was 70 employees of PT. Anela km 79 Lamongan Regency uses the Slovin formula calculation method. Data collection methods by collecting primary and secondary data. The analysis used includes instrument testing, classic assumption tests, normality tests, multiple linear regression, hypothesis testing and using multiple regression analysis using SPSS 25.0 for Windows software.The results showed that the variables Education, Age, and Work Experience simultaneously affect. While the Education variable partially affects the Employee Productivity of PT. Anela km 79 Lamongan Regency, while the variable Age and Work Experience have no partial effect on the Employee Productivity of PT. Anela km 79 Regency of Lamongan. Keywords: Education, Age, Work Experience and Employee Productivity